Multifunctional PAMAM Dendrimers Carrying SAHA, 5-FU, and a Therapeutic Gene for Targeted Co-Delivery Toward Colorectal Cancer Cells - Bulkurcuoglu, Buenyamin; Gurbuz, Mustafa Ulvi; Tyciakova, Silvia; Pavlov, Kristina; Mojzesova, Nikoleta; Matuskova, Miroslava; Tulu, Metin; Ercelen, Sebnem (WILEY-V C H VERLAG GMBH, 2024)
A promising approach to treat colorectal cancer (CRC) involves combining chemotherapy, epigenetics, and gene therapy to combat drug resistance. Multifunctional nanocarriers have emerged as a valuable tool for targeted CRC therapy. By delivering multiple treatments directly to cancer cells, these nanocarriers offer the potential for improved outcomes and reduced side effects. PAMAM-based dendrimers were functionalized with a unique combination of folic acid, 5-FU, SAHA, and plasmid DNA pCIneoGFP for targeted delivery to CRC cells. Biophysical characterizations of therapeutic loaded dendrimers and their complexes with pCIneoGFP were performed by: dynamic light scattering, fluorescence spectroscopy, and gel electrophoresis. Further, cellular analyses of dendriplexes demonstrated high transfection efficiency and anticancer activity on HCT 116 and HT-29 cell lines. We have successfully developed a multifunctional nanocarrier platform based on PAMAM dendrimers, offering a promising tool for targeted combination therapy of CRC.
Keywords: cancer; DNA condensation; gene delivery-non-viral; nanobiotechnology; PAMAM dendrimer; targeted drug delivery; COMBINATION THERAPY; COLON-CANCER; DNA; DRUG; 5-FLUOROURACIL; NANOPARTICLES; NANOCARRIERS; EXPRESSION; CHITOSANS; EFFICIENT; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology